Ignacio López-Calvo, Written in exile. Chilean fiction from 1973-present. Routledge, New York, 2001; 232 pp. - Acereda, Alberto (Nueva Revista de Filología Hispánica (NRFH), 2002)
Se reseñó el libro: Written in exile. Chilean fiction from, 1973-present.